Optimisation of anti-interleukin-6 therapy: Precision medicine through mathematical modelling - Rossi, Jean-François; Chiang, Hao-Chun; Lu, Zhao-Yang; Levon, Kalle; van Rhee, Frits; Kanhai, Karan; Fajgenbaum, David C.; Klein, Bernard (Frontiers in Immunology, 2022)
Background Dysregulated interleukin (IL)-6 production can be characterised by the levels present, the kinetics of its rise and its inappropriate location. Rapid, excessive IL-6 production can exacerbate tissue damage in vital organs. In this situation, therapy with an anti-IL-6 or anti-IL-6 receptor (IL-6R) monoclonal antibody, if inappropriately dosed, may be insufficient to fully block IL-6 signalling and normalise the immune response. Methods We analysed inhibition of C-reactive protein (CRP) – a biomarker for IL-6 activity – in patients with COVID-19 or idiopathic multicentric Castleman disease (iMCD) treated with tocilizumab (anti-IL-6R) or siltuximab (anti-IL-6), respectively. We used mathematical modelling to analyse how to optimise anti-IL-6 or anti-IL-6R blockade for the high levels of IL-6 observed in these diseases. Results IL-6 signalling was insufficiently inhibited in patients with COVID-19 or iMCD treated with standard doses of anti-IL-6 therapy. Patients whose disease worsened throughout therapy had only partial inhibition of CRP production. Our model demonstrated that, in a scenario representative of iMCD with persistent high IL-6 production not controlled by a single dose of anti-IL-6 therapy, repeated administration more effectively inhibited IL-6 activity. In a situation with rapid, high, dysregulated IL-6 production, such as severe COVID-19 or a cytokine storm, repeated daily administration of an anti-IL-6/anti-IL-6R agent, or alternating daily doses of anti-IL-6 and anti-IL-6R therapies, could neutralise IL-6 activity. Conclusion In clinical practice, IL-6 inhibition should be individualised based on pathophysiology to achieve full blockade of CRP production. Funding EUSA Pharma funded medical writing assistance and provided access to the phase II clinical data of siltuximab for analysis.